Anonymously yours - Peck, Richard (Beech Tree Books, 1995)
The popular author describes how he grew up in Decatur, Illinois, went into teaching, and eventually became a writer, incorporating his earlier experiences into novels intended to reach and change young readers
Keywords: Peck, Richard / 1934- / Juvenile literature; Peck, Richard / 1934-; Geschichte 1900-2000; Novelists, American / 20th century / Biography / Juvenile literature; Young adult fiction / Authorship / Juvenile literature; Authors, American; Alltag, Brauchtum; Decatur (Ill.) / Social life and customs / Juvenile literature; Biografie